Manajemen konflik internal dan problem eksternal: Studi kasus pada Seksi PD Pontren di Kantor Kementerian Agama Kabupaten Banyuwangi - Rosyida, Nafissatur (Maliki Interdisciplinary Journal, 2024)
In an organization certainly cannot be separated from the existence of conflict. Conflict is a point of view within the individual, but conflict does not only start from differences of opinion but conlicts can occur due to incompatibilities and nonconformances from what is expected, basically differences of opinion do not always create conflict. In an Islamic perspective, the Qur’an emphasizes the inevitability of conflict, one of which is in the Qur’an surah Al-Qashash verse 15. This study aims to indentify and describe internal and external conflict management in the Islamic education section and Islamic boarding schools at the Ministry Office Banyuwangi Regency Religion. The research method used is descriptive qualitative research. Data collection techniques were obtained from various online media reference sources, observations and the main references came from the scientific writings of UIN Malang Lecturers. The results of the study show that internal conlict in the PD Pontren section is conflict between employees caused by external problems. This is also caused by a lack of good communication between employees, causing misunderstandings. While external problems include the lack of understanding of institutional administrators such as Islamic boarding schools, madrasah diniyah and TPQ regarding the flow of services for the various assistance that will be provided. Conflict management is a process that will help manage conflicts resulting from unexpected events, prevent recurring events, and minimize the impact of events that cannot be controlled.